If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -33 = 4 Reorder the terms: -33 + 7x = 4 Solving -33 + 7x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '33' to each side of the equation. -33 + 33 + 7x = 4 + 33 Combine like terms: -33 + 33 = 0 0 + 7x = 4 + 33 7x = 4 + 33 Combine like terms: 4 + 33 = 37 7x = 37 Divide each side by '7'. x = 5.285714286 Simplifying x = 5.285714286
| r^2-11rg+28g^2= | | -8=22t-6t^2 | | 8(x-6)-3x=5(x-9)-3 | | 2x^3-32x^2-450x= | | (x+2)+7x-8=0 | | -7(v+4)+3v+7=8v+7 | | 5r+r^2-24= | | 2x+2y+80=180 | | .33x+1.33=1-.25x+1.25 | | 2x+2-5(x+1)=5x+4 | | b^2-11b+28= | | x^3+2x^2-6x-12= | | 4x^3+5x^2-8x-10= | | 0=4+2x^2 | | -4[4-(3b+4)]=5-4(3b+9) | | 4m-2.50=14.30 | | (x+2)(x+2)+8x=0 | | 2x^8+2x^7-18x^6+10x^5= | | 0=20x-2x^2-4-2x^2 | | -4[4-(3b+4)]=7-4(3b+8) | | 5x^4y^6+10x^5y^5= | | (2ln(6x)x^2)-(x^2)= | | x-3+4x=-3+11x | | -0.09p-0.04(4-4p)=0.02(p-3)-0.1 | | -6g^6+9g^4-4g^2= | | 29x+17y=-2 | | 7(y+5)-3(y+4)=19 | | X^7-7x^6-2x^5= | | -11c-(4-2c)= | | 5x-10(x+1)=-5x+22 | | 7x^8+7x-56= | | 9(z+7)-15= |